2020
DOI: 10.2147/opth.s239772
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prospective Studies of Minimally Invasive Glaucoma Surgeries: Systematic Review and Quality Assessment</p>

Abstract: Glaucoma is a common blinding disease; while there is no cure, effective treatments include medications, laser, and incisional surgery. There is significant interest from patients and doctors to develop safer surgical options throughout the spectrum of disease, to minimize treatment burden in mild glaucoma patients and to minimize risk of complications in patients needing more aggressive treatment. Surgical procedures called Minimally or Micro-Invasive Glaucoma Surgery (MIGS) are growing in popularity. Eightys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…It was a promising player in the MIGS space; however, a 5-year study found an increased rate of endothelial cell loss compared to cataract surgery alone, and in late 2018, it was recalled from the market. [ 9 ]…”
Section: Costmentioning
confidence: 99%
“…It was a promising player in the MIGS space; however, a 5-year study found an increased rate of endothelial cell loss compared to cataract surgery alone, and in late 2018, it was recalled from the market. [ 9 ]…”
Section: Costmentioning
confidence: 99%
“…Over the past decade, and with the advent of minimally invasive glaucoma surgeries (MIGSs), the field of glaucoma has witnessed an explosion of new surgical techniques and research examining their efficacy and safety [ 10 , 11 ]. MIGSs are advantageous due to their superior safety compared to traditional incisional glaucoma surgeries, minimal disruption of conjunctival and scleral tissue, faster recovery time, and compatibility with concurrent cataract surgery, while also offering a modest efficacy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The demand for minimally invasive glaucoma surgery (MIGS), which can achieve a significant reduction in intraocular pressure (IOP) with fewer adverse events than do traditional surgical procedures, has been increasing [1][2][3][4][5][6]. Trabeculotomy is a type of glaucoma surgery that is used to cleave the trabecular meshwork (TM) and the inner wall of the Schlemm's canal (SC), where the main sites of resistance to aqueous outflow are thought to reside [7][8][9].…”
Section: Introductionmentioning
confidence: 99%